(3hba LGeY GdeQMhe CMeO HGTG GdbQg eGfdjs
(3ChdgG (B:s
(3MeOkG def CPf ai JQajY GdeSGLO GdeDSSI dPcQg hYHGOJg s
(3BNQgG (B:s
(3hVQH Ydi SGbW fUg HJGQjN ef cGJHg YHjO Gddg CMeO GdYShSi habg Gddg Bejf, hYHjO Gddg YKeGf habg Gddg Cejf UhQI WHb GdCUd s
(3fSNI cJHJ HGdBdI GdcGJHIs
(3hYdjgG JhbjY GdcGJH hoeOjQ GdChbGas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B475 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs